Mortality and sexuality after diagnosis of penile cancer: a participative study. Issue 3 (14th December 2015) - Branney, Peter; Witty, Karl; Braybrook, Debbie; Bullen, Kate; White, Alan; Eardley, Ian
ABSTRACT: Survival for penile cancer is high but treatment can have a long‐term detrimental effect on urological function and quality of life. Owing to its rarity, it is difficult to include men with penile cancer in research about their condition. The aim of this study was to identify aspects of their diagnosis and treatment that they would want explored in penile cancer research. The study employed a participative, mixed qualitative methods design; it utilized focus groups and patient‐conducted interviews, combined into a 1 day 'pilot workshop'. The data were analysed using framework analysis. 'Early signs and seeking help', 'disclosure of a 'personal' cancer' and 'urological (dys)function' emerged as three key themes. Men with penile cancer want research about their condition to explore early signs and helping seeking, disclosure of a 'personal' cancer and urological (dys)function. Research could use methodologies that include consideration of the chronological narrative of the experiences of men with penile cancer, which could be applied in clinical practice by integrating opportunities to explore specific aspects of their experiences at appropriate times along the care pathway.